2008
DOI: 10.1158/1078-0432.ccr-08-0916
|View full text |Cite
|
Sign up to set email alerts
|

Potent Anticarcinoma Activity of the Humanized Anti-CD70 Antibody h1F6 Conjugated to the Tubulin Inhibitor Auristatin via an Uncleavable Linker

Abstract: Purpose: The antitubulin agent monomethyl auristatin F (MMAF) induces potent antitumor effects when conjugated via protease cleavable linkers to antibodies targeting internalizing, tumor-specific cell surface antigens. Humanized 1F6 (h1F6) is a humanized monoclonal antibody targeting CD70, a member of the tumor necrosis factor family that is expressed on hematologic malignancies and carcinomas. Here, we tested h1F6^maleimidocaproyl (mc) MMAF conjugates, consisting of an uncleavable mc linker, for their ability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 39 publications
0
71
0
Order By: Relevance
“…These data are consistent with previously published studies with the other mcMMAF ADC targeting CD70. 30,31,[33][34][35] Both ADCs induced apoptosis of CD138 1 patient MM cells following 3 days' treatment, and greater dose-dependent killing was seen by J6M0-mcMMAF than J6M0-vcMMAE ( Figure 2C). Percentages of annexin V/propidium iodide (PI) cells combined were 45.8% 6 0.5% and 74.5% 6 1.2% at 0.01 mg/mL and 1 mg/mL J6M0-mcMMAF, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These data are consistent with previously published studies with the other mcMMAF ADC targeting CD70. 30,31,[33][34][35] Both ADCs induced apoptosis of CD138 1 patient MM cells following 3 days' treatment, and greater dose-dependent killing was seen by J6M0-mcMMAF than J6M0-vcMMAE ( Figure 2C). Percentages of annexin V/propidium iodide (PI) cells combined were 45.8% 6 0.5% and 74.5% 6 1.2% at 0.01 mg/mL and 1 mg/mL J6M0-mcMMAF, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…These data are consistent with previously published studies with the other mcMMAF ADC targeting CD70. 30,31,[33][34][35] Both ADCs induced apoptosis of CD138…”
Section: Resultsmentioning
confidence: 99%
“…We chose to use auristatin, a highly potent tubulin inhibitor, because it is well characterized and can be modified for facile coupling to an antibody (10,30). Although the first generation of auristatin-linker conjugates were coupled to the N terminus of the peptide and contained a cathepsin B protease cleavage site, Doronina et al synthesized C-terminally linked derivatives that were reported to be more cytotoxic and have improved pharmacological profiles (30 (31), presumably because of degradation of the ADC in the lysosome and release of drug. Therefore, we first chose to investigate ADCs containing a noncleavable linker (nAF) coupled to the C terminus of auristatin F (AF) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The monoclonal antibodies used to measure CD30, CD70, and CD71 surface expression were BerH2 (BD Biosciences), h1F6 (14), and chimeric OKT9. Chimeric OKT9 was developed from mouse hybridoma cell line OKT9 (ATCC).…”
Section: Flow Cytometrymentioning
confidence: 99%